Fazlurrahman's Perspective Islamic Education - Imron Rasyadi (Tarbiyah Departement collaboration with AMCA, 2021)
Islamic education, which should be able to answer the challenges of the times because it has multidimensional (profane and intrinsic), in reality, is not able to display its self-image firmly. At the same time, Islamic education is needed to ensure the survival and existence of Islamic society. The purpose of this study is to reveal one side of Fazlurrahman's thoughts on Islamic education because Fazlurrahman, one of the Islamic reformers, tries to find solutions so that Islamic education is more advanced and can answer the challenges of the times. This type of research is library research, and the data source is primary and secondary data. The analytical methods used are inductive, deductive and comparative. The research approach used is qualitative. The results of this study indicate that the background of his intellectual experience influences Fazlurrahman's thoughts. He believes that many things must be reconstructed and reformed in the world of Islamic education, including the goals and the education system. The purpose of Islamic education, which has been defensive-oriented to the hereafter, must be changed to be oriented to the world and the future. In addition, Muslims must take knowledge from the modern West. Fazlurrahman's thoughts are still very relevant today.